Changes in the Small Intestine of a Cat Associated with Barium Sulphate Following Contrast Radiography. Issue 2 (February 2016) - Igarashi, H.; Oishi, M.; Ohno, K.; Tsuboi, M.; Irie, N.; Uchida, K.; Tsujimoto, H.
Summary: A 7-year-old neutered male domestic short-haired cat that had undergone contrast radiography of the bowel with barium sulphate after acute episodes of vomiting 2 months previously, was presented with chronic vomiting, anorexia and weight loss. Abdominal radiography and ultrasonography revealed residual contrast enhancement and an obstruction of the small intestine. A contracted and stenosed ileum and distal jejunum were identified by exploratory laparotomy and surgically resected; subsequently, the clinical signs resolved. Histopathological examination of the ileum revealed mucosal ulceration with severe submucosal granulation tissue formation associated with scattered foreign crystalline material. Energy-dispersive X-ray spectroscopy revealed that the crystals contained barium sulphate. This is the first report in animals of the rare complication of barium sulphate incorporation into the gastrointestinal mucosa after contrast radiography.